Integrating Digital Literacy into English for Business Communication Materials for Economics Students - Ali Syahban Amir; Muhammad Basri; Sahril Nur (Eduvelop: Journal of English Education and Development, 2026)
The rapid transformation of digital business environments has reshaped the communication competencies required of economics graduates. In this context, English for Business Communication (EBC) should be supported by digital literacy because professional communication increasingly occurs through digital platforms. However, many EBC materials used in Indonesian higher education remain text-based and provide limited exposure to authentic digital business communication. This study aimed to develop and evaluate digital literacy-integrated EBC instructional materials for economics students. Using a Research and Development design based on the ADDIE model, the study involved needs analysis, material design, expert validation, classroom implementation, and evaluation. Data were collected through questionnaires, expert appraisal forms, pre-test and post-test assessments, and student feedback. The findings showed an overall performance improvement of 17.9%, particularly in vocabulary accuracy, email coherence, business language use, and task appropriateness. Students also responded positively to the clarity, relevance, and interactivity of the developed materials. These findings indicate that integrating digital literacy into ESP-based EBC materials can strengthen students’ business communication competence and connect classroom learning with authentic digital workplace practices. Future material development should include richer multimodal resources, digital simulations, and context-based tasks to support more authentic and sustainable learning outcomes.